Penyuluhan Bahaya Narkoba dan Judi Online di Dayah Miftahus Salam Aceh Besar - Fazzan; Muhammad Kadafi; Agusmadi (Jurnal Pengabdian Masyarakat (Bisma), 2025)
Community service regarding the dangers of drugs and online gambling for Santri Dayah Mistahus Salam is implemented using the socialization method. The use of this method produces real data regarding the dangers of drugs and online gambling. The aim of socialization is to introduce people about drugs and the impacts they cause. Through various innovative counseling methods, participants showed a significant increase in knowledge regarding types of drugs, online gambling mechanisms, and their negative impacts on physical, mental and social health. More importantly, this activity succeeded in changing the participants' attitudes to be more resistant to drug abuse and online gambling. This can be seen from the increasing number of participants who are willing to become agents of change in their environment and participate in prevention efforts.